(untitled) (Revista Direito em Debate, 2020)
The present article intends to analyze the institute of the proof in the civil process, deepening the study on the magistrate’s performance in its determination and production. Passing on issues such as impartiality, role of the judge and analysis of evidence in the new Brazilian procedural model, and finally we will analyze the existence of a control in the production of evidence by the Court of Justice of Minas Gerais.